Hyaluronic Acid-Based Nanomaterials Applied to Cancer: Where Are We Now? - Vera Machado; Mariana Morais; Rui Medeiros (MDPI AG, 2022)
Cancer cells normally develop the ability to rewire or reprogram themselves to become resistant to treatments that were previously effective. Despite progress in understanding drug resistance, knowledge gaps remain regarding the underlying biological causes of drug resistance and the design of cancer treatments to overcome it. So, resistance acquisition remains a major problem in cancer treatment. Targeted therapeutics are considered the next generation of cancer therapy because they overcome many limitations of traditional treatments. Numerous tumor cells overexpress several receptors that have a high binding affinity for hyaluronic acid (HA), while they are poorly expressed in normal body cells. HA and its derivatives have the advantage of being biocompatible and biodegradable and may be conjugated with a variety of drugs and drug carriers for developing various formulations as anticancer therapies such as micelles, nanogels, and inorganic nanoparticles. Due to their stability in blood circulation and predictable delivery patterns, enhanced tumor-selective drug accumulation, and decreased toxicity to normal tissues, tumor-targeting nanomaterial-based drug delivery systems have been shown to represent an efficacious approach for the treatment of cancer. In this review, we aim to provide an overview of some in vitro and in vivo studies related to the potential of HA as a ligand to develop targeted nanovehicles for future biomedical applications in cancer treatment.